ROLE OF GRAPHIC ORGANIZERS ON LEARNING OUTCOME OF TRAINEES WITH DIVERSE LEARNING NEEDS IN KENYATTA INDUSTRIAL VOCATIONAL REHABILITATION CENTRE, NAIROBI COUNTY, KENYA - KILLY JEBET GLADYS (Machakos University Press, 2025)
Education is essential for all children regardless of their diverse learning needs in the attainment of the millennium development goals. ICT in education has offered particular benefits for learners with diverse learning needs such as visual presentations, self-paced learning, highly motivating graphics and opportunity to be in control of their own learning. However, research on the factors that contribute to the development of inclusive Graphic Organizers that are effective and customizable so as to accommodate the diverse learning needs where all learners feel valued and supported is limited. The present study sought to bridge the gap in the traditional existing literature of instructions and investigated the role of graphic organizers designed on the principles of Ausubel Advance Organizer Model theory which emphasizes the use of graphic organizers, visual cues and hierarchical structures to aid learning and knowledge retention on learning outcome of trainees with diverse learning needs. The main objective was to determine the role of Graphic Organizers on learning outcomes of trainees with diverse learning needs, assess how trainees with diverse learning needs perceive and engage with Graphic Organizers as a learning tool and establish how instructors perceive and engage with Graphic Organizers as an instructional tool at Kenyatta Industrial Vocational Rehabilitation Center in Nairobi. The study adopted a mixed methodology and an Experimental research design and in particular a pretest-posttest study employing experiment and controlled groups to measure the outcome before and after intervention. Pre-test measures were administered before the intervention to establish a baseline level of knowledge and understanding. Post-test was conducted after the intervention to determine the role of Graphic Organizers. The target population was 52 respondents who included the Centre Manager, 7 Instructors and 44 trainees with diverse learning needs who were purposely selected. The Learning Outcome was measured by specifically developed achievement test known as Criterion Referenced Test in the form of Graphic Organizer Computer Test. Questionnaires were used as a research instrument for trainees and instructors and an interview schedule was applied to the Centre Manager. The research instruments were piloted in Machakos Vocational Rehabilitation Centre, Machakos County. A reliability of 0.7 was obtained. Quantitative data was analyzed descriptively using frequencies, means, percentage and standard deviation while the narrative approach was adopted to analyze qualitative data from the Centre Manager. The inferential analysis used the t-test, chi-square techniques Wilcoxon Signed-Rank Test with the aid of Statistical Package for Social Science version 27. The hypotheses of the study were tested at ɑ=0.05 level significance. The study established the Graphic Organizers improve learning outcome of learners with diverse learning needs with reference to comprehension, organization skills and retention of learned information. Visual mapping Graphic Organizers approach was ranked first by the trainees and that instructors incorporate Graphic Organizers in all facets of training. It was discovered that insufficient training in computer applications hinders instructor’s application of the Graphic Organizers at the college. The study emphasizes on integration of Graphic Organizers into curriculum to support diverse learning needs and styles, provide training for instructors on the effective use of Graphic Organizers for different content areas and tailoring them to meet the needs of diverse learners, encourage the ministry of education, educators and policy makers to develop customizable Graphic Organizers since not all GO will work for every learner and provide options that allow learners with DLN to choose which type of GO best suits their learning preferences and needs.